Seroprevalence of Measles Antibodies in the Population of the Olomouc Region, Czech Republic-Comparison of the Results of Four Laboratories - Krupka, Michal; Matusu, Tereza; Sutova, Helena; Wezdenkova, Katerina; Vecerova, Renata; Smesna, Yvona; Kolar, Milan; Frankova, Hana Bilkova; Krivankova, Jana; Jorenek, Miroslav; Novak, Zdenek; Raska, Milan; et al. (Vaccines, 2022)
OBJECTIVES: Although the incidence of measles has decreased globally since the introduction of regular vaccination, its frequency has increased again in recent years. The study is focused on data from the Olomouc Region in the Czech Republic analyzed in four laboratories. The obtained results were compared with already published data. METHODS: The data were provided by individual laboratories in an anonymized form-age at the time of the examination, sex, and result of test. Samples were collected between June 2018 and September 2019 and evaluated on the scale positive-borderline-negative. RESULTS: A total of 7962 sera samples were evaluated using three different methods-two types of ELISA tests and CLIA. Positive result was issued in a total of 62.6 percent of samples, but the results of individual laboratories varied widely from 55.5 to 70.8 percent. However, the same trend with the highest levels of antibodies in people born before beginning of vaccination was observed. CONCLUSIONS: Data show significantly different results depending on the individual laboratories and the detection kits used. The underestimation of the proportion of positive results can cause problems in selecting individuals for revaccination with a live vaccine, which may fail in weakly positive individuals.
Keywords: ELISA; measles; Czech Republic; Olomouc region; LIAISON